Infarto do miocárdio experimental em ratos: Análise do modelo - Zornoff, Leonardo Antonio Mamede [UNESP] (2009)
One of the most often used strategies to study the physiopathological alterations caused by coronary occlusion is the use of the experimental infarction model in rats. Among other factors, this is due to the similarities in the physiopathological alterations that occur after the infarction in humans. One must consider, however, that this model has characteristics that can hinder the use as well as the interpretation of eventual outcomes. Thus, this review aims at analyzing the main characteristics of the experimental infarction model in rats, discussing the coronary occlusion technique, the consequences and the methods of morphological and functional assessment of the infarction and its clinical implications.